Legal Validity and Efficacy in the Legislative Process in Indonesia - Triya Indra Rahmawan; Moh. Fahrial Amrullah (Jurnal Penelitian, 2025)
The concepts of legal validity and legal efficacy are fundamental to assessing the overall effectiveness of legislation. Legal validity refers to the enforceability of legal norms based on procedures formally authorized by law, while legal efficacy pertains to the actual implementation and the tangible benefits experienced by society. Law Number 12 of 2011, along with its subsequent amendments—Law Number 15 of 2019 and Law Number 13 of 2022—incorporates principles and provisions that reflect an effort to integrate these two dimensions. This article aims to examine the conceptual and normative positioning of legal validity and efficacy within Indonesia’s legislative framework and to evaluate the extent to which these regulatory reforms have strengthened legislative effectiveness. Employing a normative juridical approach and legal document analysis, the study finds that public participation, the preparation of academic manuscripts, and the application of analytical tools such as ROCCIPI (Rule, Opportunity, Capacity, Communication, Interest, Process, and Ideology) and RIA (Regulatory Impact Assessment) are key mechanisms for enhancing the substantive effectiveness of Indonesian legislation.